Evaluation of the parameters of optimized coating of load graphs in the modes of synchronous operation of the power systems of Ukraine and Poland for characteristic days on the example of the actual values of the established power and load graphs - Denysov V.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
A mathematical model is proposed for optimizing the modes of using the generating capacities of the national energy system in the conditions of competition and interstate agreements and requirements, which has the advantages of adequately modeling the modes of using hydroelectric units and power units, for the mode of synchronous operation of the power systems of Ukraine and Poland for characteristic days, using the example of actual values of installed capacity and load schedules. The model belongs to the class of optimization problems with the criterion of minimizing the costs of production and import of electricity. It is implemented in the SolverStudio optimization package in the MathProg algebraic modeling language using the COIN-OR PuLP modeling language. The use of the model made it possible to explore the possibilities of optimized dispatching of generating capacities, as well as reserve capacities of large-capacity storages, the limits of permissible values for the parameters of generating and storage capacities, and cross-border flows, in which stable balanced operation of the unified energy system is possible. Model calculations of the parameters that provide optimized coverage of load curves for a typical day are performed using the example of actual values of installed capacity and load curves in 2018. The specific features accounting of the operation of generating, reserve and storage capacities of power systems in the model made it possible to determine and explore the possibilities of optimized dispatching of the components, the boundaries of permissible values of the parameters of generating and storage capacities, under which stable balanced operation of energy systems in synchronous operation modes is possible. The simulation results can be applied in the tasks of forming predictive balances for covering daily schedules of electrical loads to study the prospects for short- and long-term development of storage and generating capacities, the optimal achievable volumes of cross-border electricity flows between the energy systems of Ukraine and neighboring countries included in ENTSO-E, which is relevant in conditions of connection to these power systems.